Pandemic Grief Scale in detection of grief reaction among physicians in COVID-19 era - Samir El Sayed; Sarah Gomaa; Shereen Aboelfotoh; Mohamed El Wasify (Middle East Current Psychiatry, 2021)
Abstract Background Physicians are considered one of the most vulnerable groups who might develop pandemic grief during this critical time of COVID-19 infection, and this grief reaction might have deleterious effects on their life. This cross-sectional observational online study aimed to investigate the pandemic grief reaction among physicians and its burden on their aspects of life. Results Socio-demographic characteristics of 900 physicians were collected. The Pandemic Grief Scale (PGS) was used to detect the grief reaction among them and also Patient Health Depression Questionnaire-9 (PHQ-9) was used to evaluate the depressive manifestations. Sheehan Disability Scale was considered to investigate the burden of this grief on different aspects of life. The study revealed high mean score of Pandemic Grief Scale: 11.12 ± 2.34; the mean score of Sheehan Disability Scale was 17.63 ± 5.17, and the mean score of Patient Health Depression Questionnaire-9 was 19.89 ± 4.27. Conclusion Pandemic grief is commonly experienced by the physicians during this COVID-19 era due to sudden loss of loved one or the cases themselves. This pandemic grief has drastic effect on domains of physicians’ life.